Ectopic thyroid gland- presentation at childhood, adolescent and adult life (Bangladesh Journal of Nuclear Medicine, 2015)
Ectopic thyroid is a rare entity that can appear at any age with different presentations. In this study we are reporting four cases of ectopic thyroid gland at different ages; two cases at childhood, one at adolescent and one at adult life. Among the two children, one having ectopic thyroid at the level of hyoid bone, presented with anterior neck swelling with no other symptom and another one having a lingual ectopic thyroid presented with features of hypothyroidism and obstructive features. The cases of adolescent and adult age are very rare cases of dual ectopic thyroid and ectopic thyroid tissue coexisting with normal thyroid gland respectively. Both of them presented with anterior neck swelling, with additional complaints of dysphagia and foreign body sensation by the adolescent patient. All the cases, ectopic thyroids were detected by Ultrasonogram and confirmed by radionuclide (99mTc) thyroid scan. DOI: http://dx.doi.org/10.3329/bjnm.v17i1.22503 Bangladesh J. Nuclear Med. 17(1): 116-124, January 2014